EZH2 immunoexpression in pleomorphic adenoma and adenoid cystic carcinoma and clinicopathological features - Mariana Saturnino de NORONHA; Karolina Skarlet Silva VIANA; Maria Cássia Ferreira de AGUIAR; Cristiane Helena SQUARIZE; Mauro Henrique Nogueira Guimarães de ABREU; Elismauro Francisco MENDONÇA; Vanessa de Fátima BERNARDES (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract The aim of this study was to evaluate the expression of the EZH2 protein and describe the clinical and microscopic characteristics of adenoid cystic carcinoma (ACC) and pleomorphic adenoma (PA). The study included 16 ACC cases and 12 PA. All ACC and PA cases were positive for EZH2 and the ACC samples showed significantly higher EZH2 expression. The clinical and microscopic covariates were described in relation to EZH2 staining in ACC samples. The highest mean values of EZH2 were observed in cases with local metastasis, recurrence, perineural invasion, and predominantly cribriform growth pattern without solid areas. EZH2 is a potential marker of malignancy.